2003
DOI: 10.4049/jimmunol.170.12.5851
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Survival of Activated B Cells Requires Sustained Antigen Receptor Engagement and Phosphoinositide 3-Kinase Activation

Abstract: In this study, we investigate the extracellular and intracellular signals that drive cell cycle progression of activated B cells in the absence of T cell help. We find that brief engagement of the B cell receptor is sufficient to induce a single cell division in a fraction of cells, but that survival during successive cell divisions requires sustained receptor stimulation. In contrast, T cells have been shown previously to commit to multiple cell divisions following brief TCR engagement. Both early and late B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 30 publications
3
77
0
1
Order By: Relevance
“…It is possible that different gene response patterns to anti-Ig in the B cell subsets could dilute or cancel each other out at the population level, contributing to less up-regulation of Ccnd2 and Plk. This explanation also fits with the observation that mouse splenic B cells showed more death in response to anti-Ig than to CD40L or LPS (43)(44)(45). Another gene that was strongly induced by CD40L, CpG, IL-4, and LPS, but not by anti-Ig, is myristoylated alaninerich protein kinase C substrate (MARCKS).…”
Section: Gene Expression Change Patterns Distinguishing Anti-igsupporting
confidence: 62%
“…It is possible that different gene response patterns to anti-Ig in the B cell subsets could dilute or cancel each other out at the population level, contributing to less up-regulation of Ccnd2 and Plk. This explanation also fits with the observation that mouse splenic B cells showed more death in response to anti-Ig than to CD40L or LPS (43)(44)(45). Another gene that was strongly induced by CD40L, CpG, IL-4, and LPS, but not by anti-Ig, is myristoylated alaninerich protein kinase C substrate (MARCKS).…”
Section: Gene Expression Change Patterns Distinguishing Anti-igsupporting
confidence: 62%
“…This study demonstrated that sustained BCR signaling through PI3K is required for proliferation and survival of B cells. LY294002 and CsA were effective at blocking the activation of B cells at late time points in which Akt activation was weak and not PI3K dependent (19). This suggests that newly generated FOXO1 protein may be inefficiently phosphorylated by Akt and degraded at late times post-BCR stimulation, necessitating the newly described PI3K/Btk/calcineurin-dependent mechanism for inhibiting further expression of FOXO1 mRNA.…”
Section: Discussionmentioning
confidence: 91%
“…As a result, the cells enter and progress through the cell cycle, receiving a variety of survival signals. Each of these processes depends on PI3K (19). A major downstream target of PI3K signaling in BCR-stimulated B cells is Akt (20).…”
Section: B Cell Receptor Signaling Down-regulates Forkhead Box Transcmentioning
confidence: 99%
“…33,34 Similarly, sustained activation of the PI3K/Akt pathway is required to drive cell cycle progression in activated T-and B-cells. 35,36 Therefore, to further investigate whether insufficient activation of these kinases is responsible for the lower proliferative capacity of the prognostically favorable CLL B-cell subset, we introduced cDNA constructs encoding for constitutively active MEK2 and constitutively active Akt in primary CLL B-cells that were nonresponsive to CpG ODN-induced proliferation. Although both constructs were efficiently transfected, induction of cyclin A following CpG ODN stimulation was observed only in CLL B-cells transfected with constitutively active Akt, whereas cyclin A was not induced in cells with enforced activation of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] Although a role for JNK in B-cell proliferation has also been established, it is still not known whether quantitative differences in JNK activation can influence cell cycle progression. [37][38][39] We therefore decided to further investigate the possibility that the stronger proliferative response of progressive/V H unmutated CLL B-cells is due to increased signaling through the Akt or ERK pathway.…”
Section: Enforced Activation Of Akt Induces Cell Cycle Progression Inmentioning
confidence: 99%